Evaluation of external and internal lateral osteotomy in rhinoplasty - M Khakzad (Babol University of Medical Sciences, 2005)
Background and Objective: Rhinoplasty is one of the common operations in plastic surgery. The aim of this study was to compare the efficacy of external and internal osteotomy in rhinoplasty in Babol. Methods: This clinical trial study was conducted on patients referred to the center of plastic surgery of Babol medical university from September 2001 to May 2003. Patients chose one of two methods of the surgery (External and internal osteotomy). After surgery the rate of ecchymosis and edema, duration of resolution of edema and late complications of the surgery were evaluated. Data were analyzed by SPSS and proportions were compared by X² and Fisher’s exact test. Findings: 100 subjects with the mean age of 23.44±5.75 and 77 subjects with the mean age of 24±6.5 years were operated by internal and external osteotomy, respectively (P=0.597). Severe edema was significantly higher in patients were operated by internal lateral osteotomy than those who operated by external one (16% and 1.3%, respectively) (P=0.00001). Mean duration of the resolution of edema in patients operated in internal lateral osteotomy was significantly higher than those operated by external one (11.5±3 and 8.4±2 days, respectively) (P=0.00001). Late complications as mucocyst and step in internal lateral osteotomy occurred in 3 cases but no case was seen in the external one. Conclusion: The results showed that the rate of edema and ecchymosis and late complications in cases operated by external lateral osteotomy were lower than cases operated by internal lateral osteotomy. So it is recommended that this method of surgery is used for rhinoplasty.